Asymmetric Thickness Intracorneal Ring Segments for Keratoconus - Baptista PM (Dove Medical Press, 2020)
Pedro Manuel Baptista,1,2 João Heitor Marques,1 Miguel Mesquita Neves,1 Miguel Gomes,1,2 Luís Oliveira1 1Ophthalmology Department, Centro Hospitalar Universitário Do Porto, Porto, Portugal; 2Instituto De Ciências Biomédicas Abel Salazar, Porto, PortugalCorrespondence: Pedro Manuel BaptistaCentro Hospitalar Universitário Do Porto, Largo Prof. Abel Salazar, Porto 4099-001, PortugalTel +0035-1917868372Email pedroyybaptista@gmail.comPurpose: To describe the anatomical and functional results of the implantation of asymmetric thickness intracorneal ring segments (AS-ICRS) in eyes with keratoconus and asymmetric/irregular astigmatism (type 2 – Duck – and type 3 – Snowman – phenotypes, Fernandez-Vega/Alfonso morphologic Keratoconus classification).Materials and Methods: Retrospective observational study including 19 consecutive patients (21 eyes) with keratoconus who underwent manual implantation of the Keraring® Asymmetric ICRS (AS). Analysis included demographic and clinical data and Pentacam (Oculus®) measurements: topographic astigmatism; topographic flat meridian (K1), steepest meridian (K2) and the maximum keratometric point (Kmax); total root mean square (RMS) and high order RMS (HOA) aberrations and comatic Zernike coefficients (Z31;Z3− 1) at 0º and 90º meridians.Results: Overall mean age was 35.3± 11.7 years and median follow-up was 7.1 months (range 6– 12). At the end of follow-up, a significant improvement from baseline was achieved in both UDVA (0.24± 0.22; p=0.017) and CDVA (0.21± 0.17; p< 0.001). Regarding topographic measurements, the greatest decrease was observed in K2 (2.76± 1.9D; p< 0.001) and astigmatism (1.97± 1.5; p< 0.001). Aberrometry analysis showed a reduction of 1.27± 3.2μm in the total RMS (p=0.085), 0.24± 0.9μm in HOA (p=0.227) and 0.78± 0.5 (p< 0.001) in the 90º component of comatic aberration. The procedure effects in the CDVA, topographic and aberrometric parameters were higher in type 2 cones without statistical significance (p> 0.05 in all).Conclusion: Implantation of the Keraring® Asymmetric ICRS in keratoconus with asymmetric/irregular astigmatism allowed an improvement of several clinical, topographic and aberrometric parameters, with clinical efficacy and safety, with a tendency to a greater effect in the type 2 cones.Keywords: aberrometry, asymmetric, astigmatism, ICRS, keratoconus